Enhancing BLDC Motor Performance with Wheel-Hub Design by Modify Coil Configurations - Putranto, Rifki Dwi; Hafidz, Isa; Kholima, Henko; Putri, Nur Wahyuni (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
This paper presents an analysis of the design method of a BLDC (Brushless DC) motor with a wheel-hub structure. This study examines how variations in winding configuration affect motor performance. A 650W wheel-hub BLDC motor will be tested by modifying its stator design, including variations in the number of wires, the number of parallel circuits, and the diameter of its conductor. The test focuses on the effect of these changes on the torque, efficiency, output power and rotational speed of the motor.The test was carried out using standard sized wires. The results show that appropriate winding arrangements can increase motor torque and speed. When the parallel circuit configuration is used, the motor efficiency increases and the wire diameter is optimized. Based on the design implementation carried out, the 650W hub-type BLDC motor tested was able to achieve a maximum power of 956W, a maximum speed of 477 rpm, and a maximum torque of 41 Nm. In addition, the highest efficiency achieved was 86% at a torque of 31.8 Nm, a speed of 239 rpm, and a power of 956W.The results of this study emphasize the importance of proper winding configuration in optimizing motor performance. This winding configuration selection procedure is expected to be a reference in the manufacture of wheel-hub BLDC motors.